Bacteria Load Determination of the Intestinal Microbiota and Identification of Spiroplasma and Wolbachia in Anopheles gambiae - Sina, Haziz; Chabi-Sika, Kamirou; Ossè, Razaki; Socohou, Akim; Abibou, Ibrahim A.; Salami, Hafiz; Padonou, Germain Gil; Adjanonhoun, Adolphe; Baba-Moussa, Lamine (International Journal of Zoology, 2022)
The gut microbiota of mosquitoes is composed of a range of microorganisms. Among its microorganisms, some affect the vectorial capacity of mosquitoes. The aim of this study was to characterize some bacteria of the intestinal microbiota in Anopheles gambiae (An. gambiae) females, a major vector of malaria transmission in Benin. The symbiote bacteria of the microbiota of female laboratory An. gambiae and female wild An. gambiae were identified by the culture method. The count was done on media plate count agar (PCA), and subsequently, the bacterial load was calculated. Comparison of batches bacterial load was carried out with the variance analysis test (ANOVA). Finally, polymerase chain reaction (PCR) was performed to investigate the presence of a few bacterial genera influencing the vector capacity of An. gambiae. The study found that the microbiota of female An. gambiae is home to the bacteria belonging to the Staphylococcus, Enterobacteriaceae, and other unidentified bacterial gene regardless of its nature and condition. Similarly, there was no statistically significant difference between the bacterial load of the laboratory and wild mosquitoes depending on the parous and gorged states; on the other hand, there was a significant difference between the bacterial loads of the laboratory and wild mosquitoes according to the nulliparous and nongorged states. The search for a few bacterial genera influencing the vector capacity of female An. gambiae has been negative for Spiroplasma bacteria regardless of its nature and condition. PCR revealed the presence of Wolbachia bacteria for only gorged Kisumu sensitive An. gambiae. Wolbachia’s presence at An. gambiae suggests that this type of bacteria could be used to develop new effective and sustainable approaches in the vector control.